Effect of texturing on thermal, electric and elastic properties of MoAlB, Fe2AlB2, and Mn2AlB2. Issue 7 (July 2022) - Kota, Sankalp; Agne, Matthias T.; Imasato, Kazuki; El-Melegy, Tarek Aly; Wang, Jiayi; Opagiste, Christine; Chen, Yexiao; Radovic, Miladin; Snyder, G. Jeffrey; Barsoum, Michel W.
Abstract: Herein, MoAlB, Fe2 AlB2, and Mn2 AlB2 with textured microstructures were sinter-forged from pre-reacted preforms in a hot press at 1400, 1200, and 1050 °C, respectively. X-ray diffraction and energy dispersive X-ray spectroscopy confirmed the textured nature and high phase purities. The effect of texturing on the thermoelectric properties was evaluated by measuring thermal diffusivities, electrical resistivities, and Seebeck coefficients on the sinter-forged samples and those of less textured, reactively hot-pressed samples. While the thermoelectric properties were essentially isotropic for sinter-forged Fe2 AlB2 and Mn2 AlB2, differences included electron-dominated thermal transport in Fe2 AlB2 and phonon-dominated transport in Mn2 AlB2 over most of the 323–873 K range. Magnetic phase transitions at 281 K in Fe2 AlB2 and 308 K in Mn2 AlB2 were identified in electrical resistivity measurements. MoAlB was found to have anisotropic thermoelectric properties, with notably small relative Seebeck coefficients ranging from − 2 μV/K at 323 K and increasing to 5 μV/K at 873 K. Highlights: MoAlB, Fe2 AlB2, and Mn2 AlB2 were sinter-forged to make textured materials at 1400, 1200, and 1050 °C, respectively. The anisotropy of the thermoelectric properties depends on both the crystal structure and M-element. The textured Mn2 AlB2 and Fe2 AlB2 materials had isotropic thermoelectric properties. For MoAlB, thermal and electrical conductivities were higher perpendicular and parallel to the basal planes, respectively.